BANJARMASIN FUTSAL CENTER - Christiansyah, Kevin; Tharziansyah, Muhammad (UNIVERSITAS LAMBUNG MANGKURAT, 2020)
Banjarmasin Futsal Center appears as an answer to some problems that exist in the world of futsal in Banjarmasin. The problem is the lack of effectiveness of facilities for most futsal center in Banjarmasin. In addition, the image building of futsal centers also contributed to the problem, which is less reflect its image as a sports hall. Architecture method used in answering the problems is architectural programming method by referring to the standardization of building space in sports hall that include spaces must available in the sports hall along with the minimum standards of the room size. Representative concept also used as a support in providing the absolute picture of sports hall’s image to the public. Sports hall basically do not have special characteristics related to the image of the building contained in a theory, therefore Banjarmasin Futsal Center is designed by approaching the football stadium especially in terms of its shape so that it can be known as